Modeling and Using Context 6th International and Interdisciplinary Conference, CONTEXT 2007, Roskilde, Denmark, August 20-24, 2007, Proceedings - Kokinov, Boicho.; Kokinov, Boicho.; Richardson, Daniel C.; Richardson, Daniel C.; Roth-Berghofer, Thomas R.; Roth-Berghofer, Thomas R.; Vieu, Laure.; Vieu, Laure. (Lecture Notes in Artificial Intelligence ;, 2007)
Context a?ects a wide range of activities in humans and animals as well as in arti?cialagentsandothersystems.Theimportanceofcontextiswidelyackno- edged, and “context” has become an area of study in its own right, as evidenced bynumerousworkshops,symposia,seminars,andconferencesonthisarea.CON- TEXT,theoldestconferenceseriesfocusing oncontext,is unique inits emphasis on interdisciplinary research. Previous CONTEXT conferences have been held in Rio de Janeiro, Brazil (CONTEXT’97), Trento, Italy (CONTEXT’99, LNCS 1688), Dundee, UK (CONTEXT 2001, LNCS 2116), Palo Alto, USA (CON- TEXT 2003, LNCS 2680), and Paris, France (CONTEXT 2005, LNCS 3554). Each of these brought together researchers and practitioners from a large range of ?elds to discuss and report on context-related research and projects. The CONTEXT 2007 conference was held at Roskilde University, Denmark. The ?rst two days were devoted to workshops on speci?c areas of interest to the context community and, in parallel, the doctoralconsortium. The remaining three days featured invited talks, presentations, and posters on both theoretical and applied context research. This volume contains the papers presented at CONTEXT 2007, the Sixth International and Interdisciplinary Conference on Modeling and Using Context. There were 121 submissions to the conference. The committee decided to accept 42 papers on the basis of a thorough and highly selective review process. We believe that the papers of this volume represent a snapshot of current work and contribute to both theoretical and applied aspects of research.